In vitro treatment to improve the germination response in orophitic boreal species from northern Apennines – national park “Riserve Naturali Casentinesi”. - SGARBI, Elisabetta; GRIMAUDO, Maddalena; DEL PRETE, Carlo; DALLAI, Daniele; SOLIANI STRADI M. L (2007)
The Botanic Garden of Modena and the National Park of “Riserve Naturali Casentinesi” recently promoted an integrated in situ/ex situ conservation project, according to guidelines suggested by the Global Strategy for Plants Conservation (AA.VV., 1995; BGCI-IABG, 2000). Researches were carried out to propagate some plant species with distinctive requirements of protection. The species considered in this experimental work grow at thepresent in the Park, which represent the southernmost line of settlement for these orophytic–boreal species: Hieracium villosum L., Saxifraga oppositifolia L., Saxifraga paniculata Miller, Saxifraga moschata Wulfen, Rhynchosinapis cheiranthos (Vill.) Dandy.The goal of this research was to find useful treatments to bypass the natural dormancy of the seeds and to improve in vitro germination and growth. The seeds/achenes have been stored at 4 °C in the dark for 2 months since their collection in nature, until the beginning of treatments. The viability test, conduced applying TTC method (Van Waes, J.M. & Debergh, 1986a), gave the following positive results: H. villosum 66,6%, S. oppositifolia 73,3%, S. paniculata 40%, S. moscata 43,3%, R. cheiranthos 76,6%. Seed/achenes were sterilized/scarificated with a solution of NaOCl (1.5 % Chlorine available + 1% Tween 80), sown on MS1⁄2 culture medium, at half strength of salts as control medium and maintained under artificial light, 12 hours photoperiod (control conditions). At the same time, the specimens were differently processed in order to break the dormancy.Preliminary tests on Hieracium villosum achens, treated with and without pre-chill treatments (4 °C for 8 weeks), did not give significantly different results. Furthermore these results were affected by repeated contaminations that occurred after some days of culture. More effective methods to sterilize the achenes must be applied. Germination percentages reached 30% (mean value). Plantlets grown in vitro were successfully transferred in pots and acclimatised.Seeds of Saxifraga ...